Sustainable development and global finance : a cultural discourse analysis of Corporate Social Responsibility and Socially Responsible Investing - Hempshall, Kerri-Anne (SLU/Dept. of Urban and Rural Development, 2019)
This thesis explores the cultural discourse of two programs relating Sustainable Development (SD) to professionals within the Global Financial Sector. Through cultural discourse analysis, it has set out to explore and compare discussions surrounding Corporate Social Responsibility and Socially Responsible Investing in regard to the meaning of these programs for individuals implementing them. It has found that professionals working within and in partnership with global financial companies interpret the meaning of SD differently according to their cultural discourse. Beyond this, professionals have the opportunity to reshape current discourses through introducing new understandings and that greater collaboration is essential for generating better solutions to SD related problems. This research fits into a growing field of study contributing to the communicative view of Corporate Social Responsibility and institutional change as well as arguments calling for greater consideration of culture within sustainable development debates. In light of the 2015 Sustainable Development Manifesto and ‘Positive Impact Finance Initiative’ set out by the UN Environment Program 2017, along with increasing interest in CSR, SRI and institutional engagement in sustainable development principles, this is a topic of growing importance policy makers and company managers alike.